ANALISIS KINERJA INDUSTRI PERBANKAN NASIONAL PASCA COVID-19 - Roni, Faizal; Rafik, Ahmad; Lidwan, Nanang; Siagian, Sabaruddin (JURNAL LENTERA AKUNTANSI, 2023)
The purpose of scientific writing is to analyze the performance of the banking industry, related to liquidity performance, credit disbursement and processing of non-performing loans, management of third party funds (DPK), profitability or ROA, and post-Covid-19 banking capital or CAR. The research sample used is a conventional commercial bank (BUK). The data used is secondary data taken from OJK. As a result, overall banking performance after the Covid-19 crisis has been satisfactory. As an individual result, post-Covid-19 banking liquidity is very good, credit disbursement performance has returned to normal and the management of non-performing loans is consistently in a safe position. Meanwhile, the performance of third party fund management also greatly improved. In addition, bank profitability has recovered to the level it was before the Covid-19 crisis and banking capital or CAR during the post-Covid-19 crisis has remained strong to finance the elimination of problem loans.Key words: Liquidity, Credit, NPL, DPK, ROA and CAR.